Sensible Heat Bean Cooker - Lwiwa, Casiana B.; Nydal , Ole J. (Tanzania Journal of Engineering and Technology, 2025)
Alternative cooking energy to replace wood fuels is needed in the African context. Liquified Natural Gas (LNG) is a solution but is still based on burning fossil fuel. Electrical cookers can be an alternative as well. However, for off-grid systems this means electrical batteries are required, as the solar electricity from Photovoltaic (PV) panels is intermittent, and as cooking is also to be made after sunset. Heat storage technologies can provide solutions where available energy is stored in the form of heat for cooking when needed. The challenge is then to develop systems which are robust, safe, and technically simple. A very simple small-scale solution is demonstrated here, for the particular case of cooking beans. An insulated iron cylinder is heated, either in a solar concentrator or by PV-powered heating elements. The stored heat can then be calibrated to the cooking of a given volume of beans. After the cylinder has reached the calibrated temperature during the charging, the pot can be placed and left on the top of the cylinder. When the energy is depleted, the beans should be ready cooked.